Transformasi Nilai Hijrah dalam Pembentukan Karakter Religius Remaja melalui Kegiatan Gebyar Muharram: Studi Kualitatif di Desa Serapuh Kabupaten Langkat - Hayatun Sabariah; Dinda Rispani; Wisufia salma; Sabila Azhara (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to describe the transformation of hijrah values among adolescents through the implementation of the Gebyar Muharram program in Serapuh Village, Langkat Regency. The study highlights the internalization of hijrah values through community-based religious activities that actively engage adolescents as both participants and organizing committee members, enabling them to develop character, leadership, responsibility, and social awareness. It also emphasizes the collaboration among the village government, religious leaders, parents, mosque administrators, and the community in supporting non-formal Islamic education. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving the village head, religious leaders, committee members, parents, and participating adolescents. The data were analyzed through data collection, reduction, presentation, and conclusion drawing. The findings indicate that Gebyar Muharram is conducted annually through various activities, including Islamic competitions, religious lectures, dhikr, collective prayers, and charity programs for orphans. Adolescents’ involvement in organizing and participating in these activities provides meaningful learning experiences that strengthen responsibility, teamwork, leadership, and social concern. Furthermore, the transformation of hijrah values is reflected in increased enthusiasm for worship, improved moral behavior, stronger self-confidence, and greater awareness of self-improvement based on Islamic teachings. The study concludes that Gebyar Muharram functions not only as a commemoration of the Islamic New Year but also as an effective model of community-based non-formal Islamic education for fostering adolescents’ character and religious development.